Personality Types in the Space of Amorality and Schizotypy: Empirical Evidence From the Samples of Prisoners and From General Population - Petrović, Boban; Međedović, Janko; Kujačić, Daliborka (Zbornik Instituta za kriminološka i sociološka istraživanja, 2014)
Contrary to the importance of constructs of amorality and shizotypy, especially for understanding antisocial and criminal behaviour, there is little research aimed at investigating their relationships at various levels of their intensity. This research aimed to investigate whether it is possible to extract meaningful psychological types in a common space of amorality and schizotypy, and a deeper understanding of detected types on the basis of different psychological variables. In this sense, in the context of this research, two studies were conducted. In the first study, instruments for assessment of Amorality and Schizotypy, which were used for defining the clusters of respondents, were applied to the sample of 223 males from the prison population. Detected clusters were further validated in the common space of Five Factor personality traits, Psychopathy and measures of recidivism. In the second one, data about Amoral and Schizotypy, as well as basic personality traits defined through Eisenck's model of personality, and also intelligence, were collected from the sample of 318 male respondents from the general population. Results showed that using cluster analysis, it is possible to identify three to four clusters of respondents in both samples. It is especially important that subtypes within the cluster of amoral individuals were identified – the subtypes of schizotypal amoral and integrated amoral individuals. Schizotypal amorals are characterised by dispositions, which indicated tendency toward more severe forms of criminal activities, but, more important, toward mental dysfunctions (impulsivity, introversion, neuroticism, psychoticism, lower intelligence). Profile of integrated amorals is closer to the concept of "successful psychopathy" (conscientiousness, extraversion, emotional stability). The results of this research are indicative of a deeper understanding of criminal behaviour.